2005
DOI: 10.1037/0021-9010.90.4.616
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Model of Safety Climate: Cross-Level Relationships Between Organization and Group-Level Climates.

Abstract: Organizational climates have been investigated separately at organization and subunit levels. This article tests a multilevel model of safety climate, covering both levels of analysis. Results indicate that organization-level and group-level climates are globally aligned, and the effect of organization climate on safety behavior is fully mediated by group climate level. However, the data also revealed meaningful group-level variation in a single organization, attributable to supervisory discretion in implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
847
3
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,028 publications
(910 citation statements)
references
References 61 publications
51
847
3
9
Order By: Relevance
“…The present study adopts a multi-dimensional approach to safety climate (Cooper and Philips, 2004;Zohar and Luria, 2005) and demonstrates (1) the differential direct impact of these safety climate dimensions (management commitment to safety, priority of safety, pressure for production) on risk behavior and (2) a complex relationship between these three safety climate dimensions in influencing unsafe behavior at work. In support of our hypothesis, and in line with previous research examining their impact on safety performance, we found that employee risk behavior was negatively related to management commitment and priority of safety, and positively related to pressure for production (see Hypothesis 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study adopts a multi-dimensional approach to safety climate (Cooper and Philips, 2004;Zohar and Luria, 2005) and demonstrates (1) the differential direct impact of these safety climate dimensions (management commitment to safety, priority of safety, pressure for production) on risk behavior and (2) a complex relationship between these three safety climate dimensions in influencing unsafe behavior at work. In support of our hypothesis, and in line with previous research examining their impact on safety performance, we found that employee risk behavior was negatively related to management commitment and priority of safety, and positively related to pressure for production (see Hypothesis 1).…”
Section: Discussionmentioning
confidence: 99%
“…senior manager, supervisor) is however ambiguous in some studies despite the large differences in their roles and perceived influence by employees (Clarke, 1999;Flin et al, 2000). In the present study we focus on employees' perceptions of senior management commitment to safety as senior managers "undoubtedly set the tone and tempo for organizational atmosphere, establish priorities and allocate resources" (Flin et al, 2000, p. 186) and as their safety policies, procedures, and actions are critical in limiting supervisor discretion in policy implementation (Zohar and Luria, 2005).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Since the landmark paper on this topic by Zohar (1980) some 28 years ago, safety climate research has evolved to embrace a range of themes. An ongoing part of the research effort is devoted to improving measures of safety climate (e.g., Flin et al, 2000;Hahn and Murphy, 2008;Zohar and Luria, 2005) or adapting those measures to particular cultures (e.g., Lin et al, 2008). Other researchers have focused on identifying safety climate variables with the aim of constructing models to explain the interactions among the variables and their impact on safety performance (e.g., Fogarty, 2004Fogarty, , 2005Hahn and Murphy, 2008).…”
Section: Models Of Unsafe Behaviormentioning
confidence: 99%